2011
DOI: 10.1126/scitranslmed.3001875
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Methylomes Establish an Epigenomic Foundation for Metastasis

Abstract: Cancer-specific alterations in DNA methylation are hallmarks of human malignancies; however, the nature of the breast cancer epigenome and its effects on metastatic behavior remain obscure. To address this issue, we used genome-wide analysis to characterize the methylomes of breast cancers with diverse metastatic behavior. Groups of breast tumors were characterized by the presence or absence of coordinate hypermethylation at a large number of genes, demonstrating a breast CpG island methylator phenotype (B-CIM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
227
4
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 246 publications
(246 citation statements)
references
References 68 publications
12
227
4
2
Order By: Relevance
“…In our study, we found that a distinct population of both ER þ and ER À tumours are associated with extensive methylation across the DMRs, more representative of a CpG island methylator phenotype (CIMP) 29 . Interestingly, a previous report describes the breast-CIMP (B-CIMP) group comprising solely ER þ tumours 16 ; however, our results show that coordinated hypermethylation can also occur in ER À disease. We also identified three distinct methylation clusters of TNBC tumours based on our DMRs.…”
Section: Articlecontrasting
confidence: 53%
See 3 more Smart Citations
“…In our study, we found that a distinct population of both ER þ and ER À tumours are associated with extensive methylation across the DMRs, more representative of a CpG island methylator phenotype (CIMP) 29 . Interestingly, a previous report describes the breast-CIMP (B-CIMP) group comprising solely ER þ tumours 16 ; however, our results show that coordinated hypermethylation can also occur in ER À disease. We also identified three distinct methylation clusters of TNBC tumours based on our DMRs.…”
Section: Articlecontrasting
confidence: 53%
“…We identified 308 genes affected by promoter hypermethylation and functional analysis revealed significant enrichment of genes and transcription factors involved in development and differentiation, as well as DNA binding, homeobox proteins and transcriptional regulation. Hypermethylation of homeobox genes has been previously reported in breast cancer and associated with disease progression and poor patient prognosis 15,16,34,35 . Genes encoding glycoproteins were also enriched in the functional analysis.…”
Section: Articlementioning
confidence: 99%
See 2 more Smart Citations
“…Molecular classification of tumours could also guide treatment with broad-acting epigenetic drugs. DNMTis could be particularly useful in treating the subset of colorectal, brain and breast tumours that have a high degree of CpG island promoter hyper-methylation (Toyota et al, 1999;Noushmehr et al, 2010;Fang et al, 2011), which is now being clinically tested in colorectal cancer patients.…”
Section: Future Directions For Epigenetic Therapymentioning
confidence: 99%